Modelling B2C e-businesses in fast-growing industries using system dynamics. (31st August 2005) - Fang, Yulin
Most existing econometric studies have approached the issue of internet-based Business-to-Consumer (B2C) operation by analysing one or two specific relations. Few studies have examined the entire dynamics of online (internet-based B2C) and offline (traditional brick and mortar) operation in fast-growing industries. Taking the System Dynamics (SD) perspective, this paper offers a comprehensive conceptual model (i.e., causal loop diagrams) that portrays dynamic processes of simultaneously running online and offline businesses in fast-growing industries. Major functional areas such as R&D, manufacturing, marketing, product delivery, after sales service, online store construction, and online versus offline customer interflow are included in the causal loop diagram. Five reinforcing loops and three balancing loops plausibly influencing corporate performance are identified and discussed. Implications of the conceptual model for researchers and practitioners in fast-growing industries are also discussed.